Calibrating the amplitude source location (ASL) method by using active seismic sources: An example from Te Maari volcano, Tongariro National Park, New Zealand. Issue 8 (24th April 2017) - Walsh, B.; Jolly, A. D.; Procter, J.
Abstract: A frequently applied amplitude source location (ASL) method is here calibrated and optimized by using active seismic sources located at the surface of a dry stream channel. The ASL produced location discrepancies larger than 1.0 km laterally and 500 m in depth by using independently determined velocity model, attenuation, and site amplification factors (AFs). Sensitivity tests for ASL input parameters show that attenuation and velocity have moderate influence on the location but are easy to independently constrain. AFs are shown to strongly influence the location, and their application may introduce substantial location uncertainties. Model uncertainties are accommodated with either lateral or depth changes depending on the input parameters, station corrections, and the source‐station geometry. Key Points: First calibration of amplitude source location (ASL) method using active seismic sources Application of known velocity and decay model constraints provide substantial location improvements Standard errors from amplification factors (AFs) yield substantial ASL location errors